PENGARUH EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT TATANAN RUMAHTANGGA PADA PASANGAN USIA SUBUR TERHADAP SIKAP PENCEGAHANDIARE PADA BALITA DI DESA DOREKECAMATAN BALI BELO KABUPATEN BIMA - Mustikaratu; I Made Eka Santosa; I Gusti Ayu Mirah Adhi; Robiatul Adawiyah; Ni Made Sumartyawati (LPPM STIKES Mataram, 2024)
Introduction: Diarrhea is an increase in the frequency of faces caused by infectious agents in the gastrointestinal tract and often occurs in toddlers (Juffrie et al., 2019). Occurs at least 3 times in 24 hours, signs and symptoms of diarrhea are abdominal cramps, abdominal pain, nausea and vomiting. The application of clean and healthy living behavior in households can prevent diarrheal diseases. Objective: This study aims to determine the effect of education on clean and healthy living behavior in the household of couples of childbearing age on the attitude of preventing diarrhea in children under five in Dore Village, Pali Belo District, Bima Regency. Method: The design of this study used a pre-experimental design with a research design of One group pretest-posttest design. The sampling technique used is total sampling. The study population was 60 couples of childbearing age in Dore Village, Pali Belo District, Bima Regency. The sample is determined by a total sampling obtained as many as 60 respondents. Collecting data about diarrhea prevention attitudes using a questionnaire sheet and analyzing data using a statistical paired sample t-test with an error rate of 5%. Results : The level of pre-test attitude was in the negative category as much as 76.67%, positive attitude 23.33% and negative attitude during post-test 13.33% and positive attitude increased by 86.67%. Conclusion: There is an Effect of Education on Clean and Healthy Living Behavior in Households of Couples of Childbearing Age on Attitudes to Prevent Diarrhea in Toddlers in Dore Village, Pali Belo District, Bima Regency.